ARTS (Aspiration–Retriever Technique for Stroke): Initial clinical experience. Issue 3 (June 2016) - Massari, Francesco; Henninger, Nils; Lozano, Juan Diego; Patel, Anand; Kuhn, Anna Luisa; Howk, Mary; Perras, Mary; Brooks, Christopher; Gounis, Matthew J; Kan, Peter; Wakhloo, Ajay K; Puri, Ajit S
Background: A new generation of highly navigable large-bore aspiration catheters and retriever devices for intracranial mechanical thrombectomy has markedly improved recanalization rates, time and clinical outcomes. We report collected clinical data utilizing a new technique based on combined large lumen aspiration catheter and partially resheathed stent retriever (ARTS: Aspiration (catheter)–(stent) Retriever Technique for Stroke). This technique is applied, especially in presence of bulky/rubbery emboli, when resistance is felt while retracting the stent retriever; at that point the entire assembly is locked and removed in-toto under continuous aspiration with additional flow arrest. Methods: A retrospective data analysis was performed to identify patients with large cerebral artery acute ischemic stroke treated with ARTS. The study was conducted between August 2013 and February 2015 at a single high volume stroke center. Procedural and clinical data were captured for analysis. Results: Forty-two patients (median age 66 years) met inclusion criteria for this study. The ARTS was successful in achieving Thrombolysis in Cerebral Infarction (TICI) ≥2b revascularization in 97.6% of cases (TICI 2b = 18 patients, TICI 3 = 23 patients). Patients' median National Institutes of Health Stroke Scale score at admission was 18 (6–40). A 3-month follow-up modified Rankin Scale value of 0–2 was achieved in 65.7% of the successfully treated patients (average 2.4). Two patients (4.8%) developed symptomatic intraparenchymal hemorrhages. Six procedure unrelated deaths were observed. Conclusions: We found that ARTS is a fast, safe and effective method for endovascular recanalization of large vessel occlusions presenting within the context of acute ischemic stroke.